Inhibitory Effect of Paquinimod on a Murine Model of Neutrophilic Asthma Induced by Ovalbumin with Complete Freund’s Adjuvant - Jong-Uk Lee; Jong Sook Park; Ji Ae Jun; Min Kyung Kim; Hun Soo Chang; Dong Gyu Baek; Hyun Ji Song; Myung-Sin Kim; Choon-Sik Park (Canadian Respiratory Journal)
Background. Quinoline-3-carboxamides have been used to treat autoimmune/inflammatory diseases in humans because they inhibit the functions of S100 calcium-binding protein A9 (S100A9), which participates in the development of neutrophilic inflammation in asthmatics and in an animal model of neutrophilic asthma. However, the therapeutic effects of these chemicals have not been evaluated in asthma. The purpose of this study was to evaluate the effect of paquinimod, one of the quinoline-3-carboxamides, on a murine model of neutrophilic asthma. Methods. Paquinimod was orally administered to 6-week-old C57BL/6 mice sensitized and challenged with ovalbumin (OVA)/complete Freund’s adjuvant (CFA) and OVA. Lung inflammation and remodeling were evaluated using bronchoalveolar lavage (BAL) and histologic findings including goblet cell count. S100A9, caspase-1, IL-1β, MPO, IL-17, IFN-γ, and TNF-α were measured in lung lysates using western blotting. Results. Paquinimod restored the enhancement of airway resistance and the increases in numbers of neutrophils and macrophages of BAL fluids and those of goblet cells in OVA/CFA mice toward the levels of sham-treated mice in a dose-dependent manner (0.1, 1, 10, and 25 mg/kg/day, p.o.). Concomitantly, p20 activated caspase-1, IL-1β, IL-17, TNF-α, and IFN-γ levels were markedly attenuated. Conclusion. These data indicate that paquinimod effectively inhibits neutrophilic inflammation and remodeling in the murine model of neutrophilic asthma, possibly via downregulation of IL-17, IFN-γ, and IL-1β.